Estrategias didácticas para estudiantes con discapacidad auditiva - Loayza Erreis, Marcbe Desiree; Suquilanda Domínguez, Gina Lilibeth (Machala, Universidad Técnica de Machala, 2022)
The research project addresses the issue of teaching strategies for special educational needs in students with hearing impairment of the Fiscal School "03 de diciembre" in the city of Machala during the period 2021 - 2022. The present study consists of using a didactic guide of communicative strategies as a contribution to the teachers during the process of teaching students with hearing impairment, due to the fact that in the institution there was a deficiency in the use and manipulation of strategies and techniques to teach classes in a dynamic and effective way, for this reason the students with hearing impairment have been affected, since with them we must stop ways of teaching them and they can understand, so that they can improve their communication style and progress their learning in a significant way.Through this research we will try to give some solutions to this problem considering that all research must have an answer to a certain problem, for the same reason this study has options of the use of a didactic guide of communicative strategies that help educators to orient themselves in a better way to favor children with hearing impairment and thus improve their school performance.
El proyecto de investigación aborda la temática de las Estrategias didácticas para necesidades educativas especiales en estudiantes con discapacidad auditiva de la Escuela Fiscal “03 de diciembre” en la ciudad de Machala durante el periodo 2021 – 2022. El presente estudio consiste en emplear una Guía didáctica de estrategias comunicativas como aporte a los docentes durante el proceso de enseñanza a estudiantes con discapacidad auditiva, debido a que en la institución se constató deficiencia en el uso y manipulación de las estrategias y técnicas para impartir clases de manera dinamica y eficaz, por esta razón se ha visto afectados los estudiantes que carecen de discapacidad auditiva ya que con ellos se debe de detener formas de enseñarles y puedan comprender, para que así puedan mejorar su estilo de comunicación y progresar su aprendizaje de manera significativa.
Keywords: ESTRATEGIA DIDACTICA; DISCAPACIDAD AUDITIVA; ESTRATEGIA COMUNICATIVA; CLASE AULICA; ENSEÑANZA-APRENDIZAJE